A kind of admixture for concrete anti-sticking and preparation method thereof
Through scientific proportioning and preparation technology, a blender for concrete anti-blocking was developed, which solved the problems of difficulty in selecting existing anti-blocking agents, harmful components and insufficient performance, and achieved efficient, environmentally friendly and easy-to-use anti-blocking effect, significantly improving the construction performance and quality of concrete.
Patent Information
- Application Number
- CN202410910116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Existing concrete anti-adhesive agents have difficulties in selecting, may contain harmful chemical components and insufficient performance, making it difficult to meet the needs of modern construction projects for efficient, environmentally friendly and easy-to-use anti-adhesive agents.
A blender is used, and its raw materials include wollastonite, talc, butyl acrylate, polyoxyethylene stearate, pozzolan, diatomaceous earth, surfactant and additives. Through scientific proportioning and preparation processes, a concrete anti-adhesion blender with excellent properties is formed.
It significantly improves the flowability and lubricity of concrete, reduces adhesion, improves the quality and construction efficiency of concrete, and ensures environmental protection and ease of use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to an admixture for concrete anti-sticking and a preparation method thereof. Background Art
[0002] Concrete, as a material widely used in the field of civil engineering, plays a pivotal role in the construction of buildings, bridges, roads and various infrastructures. Its unique advantages lie in its excellent compressive strength and good durability, making it an indispensable element in the field of modern construction.
[0003] In the application process of concrete, the anti-sticking problem cannot be ignored. Due to its sticky characteristics, concrete is very likely to leave difficult-to-remove residues on molds, tools or transportation equipment if appropriate anti-sticking measures are not taken. This not only increases the difficulty of work, but is also likely to have a negative impact on construction quality and efficiency.
[0004] However, there are still many challenges in the current concrete anti-adhesion. First, different concrete mixes and construction environments have different requirements for anti-adhesion agents, which brings certain difficulties to the selection and application of anti-adhesion agents. Secondly, some traditional anti-adhesion agents may contain chemical components that are harmful to the environment. Furthermore, with the continuous advancement of construction technology, the performance requirements for anti-adhesion agents are also increasing, and more efficient, durable and easy-to-use anti-adhesion agents are needed to meet market demand.
[0005] Therefore, inventing a kind of admixture for concrete anti-sticking has become the current problem that needs to be solved urgently. Summary of the invention
[0006] In view of this, the present invention proposes an admixture for concrete anti-sticking and a preparation method thereof, aiming to provide an efficient, environmentally friendly and easy-to-use concrete anti-sticking admixture to solve the anti-sticking problem of concrete in application.
[0007] The present invention provides an admixture for concrete anti-adhesion, wherein the raw materials of the admixture include:
[0008] Wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactants and additives;
[0009] The surfactant includes sodium alkylbenzene sulfonate, sodium stearate or sodium lauryl sulfate;
[0010] The auxiliary agents include defoamers, toughening agents and anti-aging agents.
[0011] Preferably, the weight ratio of wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactant and additive is 4-5:1-2:3-4:2-3:5-6:4-5:0.5-1:0.2-0.3.
[0012] Preferably, the defoaming agent includes a silicone defoaming agent or a polyether defoaming agent.
[0013] Preferably, the toughening agent comprises ethylene-vinyl acetate copolymer.
[0014] Preferably, the preparation method of the ethylene-vinyl acetate copolymer comprises:
[0015] Ethylene and vinyl acetate monomers are mixed, and an ethylene-vinyl acetate copolymer is prepared by polymerization reaction under the action of a catalyst;
[0016] Wherein, the weight ratio of ethylene to vinyl acetate monomer is 7-8:2-3;
[0017] During the polymerization process, the reaction temperature is 60-80°C and the reaction time is 4-6 hours.
[0018] Preferably, the catalyst is a mixture of ammonium persulfate and sodium bisulfite, and the amount of the catalyst added is 0.5% of the total weight of ethylene and vinyl acetate monomers;
[0019] Wherein, the weight ratio of the ammonium persulfate to sodium bisulfite is 1:1.
[0020] Preferably, the anti-aging agent includes an ultraviolet absorber and an antioxidant.
[0021] Preferably, the preparation method of the admixture for concrete anti-sticking comprises:
[0022] Wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture;
[0023] Mixing butyl acrylate, polyoxyethylene stearate and a surfactant to form a mixed liquid;
[0024] Adding the basic admixture into the mixed liquid while stirring to obtain a mixture;
[0025] Add the defoamer, toughening agent and anti-aging agent into the mixture, and continue stirring until the mixture is completely uniform to obtain an admixture for concrete anti-sticking.
[0026] Preferably, when wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture, the particle size of the basic admixture is 50-100 μm.
[0027] Preferably, during the preparation process, when butyl acrylate, polyoxyethylene stearate and a surfactant are stirred to form a mixed liquid, the stirring temperature is 30-50° C. and the stirring speed is 200-400 rpm.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The admixture of the present invention has significantly improved performance and can effectively solve the adhesion problem of concrete during construction and use. Since multiple functional raw materials such as wollastonite, talcum powder, butyl acrylate, etc. are added to the admixture, the interaction between them makes the concrete have better fluidity and lubricity during mixing, pouring and curing, effectively reduces the adhesion of the concrete surface, thereby improving the quality of the concrete and the construction efficiency.
[0030] Firstly, as the basic raw materials of admixtures, wollastonite and talc not only have good physical properties, such as high hardness and good wear resistance, but also can increase the density and strength of concrete. At the same time, they can also effectively improve the microstructure of concrete and improve the impermeability and durability of concrete.
[0031] Secondly, as organic components of admixtures, butyl acrylate and polyoxyethylene stearate can react chemically with cement hydration products in concrete to form a dense protective film, thereby reducing the adhesion of the concrete surface. In addition, they can also improve the construction performance of concrete, such as reducing the viscosity of concrete and improving the fluidity of concrete.
[0032] In addition, the addition of surfactants, defoamers, toughening agents and anti-aging agents further enhances the performance of admixtures. Surfactants can reduce the surface tension of concrete, making it easier for concrete to flow and spread; defoamers can effectively eliminate bubbles in concrete, improving the density and strength of concrete; toughening agents can increase the toughness and ductility of concrete and reduce the brittleness of concrete; anti-aging agents can delay the aging process of concrete and extend the service life of concrete.
[0033] Finally, the admixture preparation process of the present invention is simple, easy to operate, and the raw materials are widely available and low in cost. By accurately controlling the proportions and preparation conditions of the raw materials, a concrete anti-sticking admixture with stable performance and reliable quality can be prepared. The admixture is not only suitable for various types of concrete, but also can be used under different construction conditions, and has broad application prospects and market demand. DETAILED DESCRIPTION
[0034] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0035] The present invention provides an admixture for concrete anti-sticking, and the raw materials of the admixture include:
[0036] Wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactants and additives;
[0037] The surfactant includes sodium alkylbenzene sulfonate, sodium stearate or sodium lauryl sulfate;
[0038] The auxiliary agents include defoamers, toughening agents and anti-aging agents.
[0039] It is understood that the present invention aims to provide a high-performance concrete anti-adhesion admixture, which is designed to improve various properties of concrete, such as reducing its adhesion, improving its durability and workability. The main raw materials of the admixture are composed of wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, etc. These raw materials are scientifically proportioned and processed to effectively improve the overall performance of concrete.
[0040] Among the above raw materials, surfactant is a key component, which includes sodium alkylbenzene sulfonate, sodium stearate or sodium dodecyl sulfate. The addition of these surfactants can improve the fluidity of concrete and reduce the adhesion between cement particles, thereby reducing the adhesion of concrete and preventing poor adhesion during use.
[0041] In addition, the present invention also provides a series of additives to further optimize the performance of the admixture. These additives include defoamers, which are used to reduce bubbles generated during the mixing and pouring of concrete and improve the compactness and strength of concrete; toughening agents, which are used to improve the toughness and crack resistance of concrete; and anti-aging agents, which are used to improve the durability of concrete and prevent it from prematurely aging during use.
[0042] In general, the present invention provides a concrete anti-adhesion admixture with excellent performance, which can effectively improve the performance of concrete and meet the needs of modern construction engineering through scientific proportioning and selection of raw materials, as well as the addition of surfactants and additives.
[0043] In a preferred embodiment of the present application, the weight ratio of wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactant and additive is 4-5:1-2:3-4:2-3:5-6:4-5:0.5-1:0.2-0.3.
[0044] It is understandable that in this optimized embodiment, the use ratio of raw materials is accurately formulated to achieve the best results. Specifically, the ratio range of wollastonite, talcum powder, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactant and auxiliary agent has been clearly set to 4-5:1-2:3-4:2-3:5-6:4-5:0.5-1:0.2-0.3 (weight ratio). This ratio range is verified by repeated experiments to ensure that the final product has excellent performance. Under this ratio, the synergistic effect between each raw material is maximized, and the improvement of product performance is jointly promoted. Therefore, the present embodiment provides a scientific and effective way to prepare high-performance products.
[0045] In a preferred embodiment of the present application, the defoaming agent includes a silicone defoaming agent or a polyether defoaming agent.
[0046] It is understandable that the defoamer used in this embodiment is mainly based on silicone or polyether defoamers. These two defoamers show excellent performance in the defoaming process and can effectively remove foam in the liquid, thereby achieving the purpose of improving production efficiency and product quality.
[0047] In a preferred embodiment of the present application, the toughening agent includes ethylene-vinyl acetate copolymer.
[0048] It is understandable that the toughening agent involved in this embodiment is mainly composed of a copolymer of ethylene and vinyl acetate. This material is carefully selected and proportioned to improve the toughness and impact resistance of the final product, so that it can show more outstanding performance when facing external pressure or impact. In this way, not only can the physical properties of the material be significantly improved, but also its application range can be broadened, so that it can be effectively used in more fields.
[0049] In a preferred embodiment of the present application, the method for preparing the ethylene-vinyl acetate copolymer comprises:
[0050] Ethylene and vinyl acetate monomers are mixed, and an ethylene-vinyl acetate copolymer is prepared by polymerization reaction under the action of a catalyst;
[0051] Wherein, the weight ratio of ethylene to vinyl acetate monomer is 7-8:2-3;
[0052] During the polymerization process, the reaction temperature is 60-80°C and the reaction time is 4-6 hours.
[0053] It is understood that the present embodiment relates to a method for preparing ethylene-vinyl acetate copolymer. Specifically, the preparation method comprises the following steps: first, ethylene and vinyl acetate monomers are mixed. This step is the key to the entire preparation process because it is necessary to ensure that ethylene and vinyl acetate monomers can be fully mixed so that they can react evenly in the subsequent polymerization reaction. After mixing, a catalyst needs to be introduced. The role of the catalyst here is to promote the polymerization reaction of ethylene and vinyl acetate monomers. Through this reaction, ethylene-vinyl acetate copolymer can be prepared. It is worth noting that the weight ratio of ethylene and vinyl acetate monomers needs to be controlled between 7-8:2-3, and this ratio can ensure that the prepared copolymer has excellent properties. During the polymerization reaction, the reaction temperature and reaction time also need to be controlled. Specifically, the reaction temperature should be between 60-80°C, and the reaction time should be between 4-6 hours. The control of these two parameters can ensure the smooth progress of the polymerization reaction and can improve the yield and purity of the copolymer. It can be seen from the above examples that the preparation method of ethylene-vinyl acetate copolymer is simple and effective. Through this method, ethylene-vinyl acetate copolymer with excellent performance can be obtained.
[0054] In a preferred embodiment of the present application, the catalyst is a mixture of ammonium persulfate and sodium bisulfite, and the amount of the catalyst added is 0.5% of the total weight of ethylene and vinyl acetate monomers;
[0055] Wherein, the weight ratio of the ammonium persulfate to sodium bisulfite is 1:1.
[0056] It is understood that this embodiment selects a specific catalyst combination, i.e., a mixture of ammonium persulfate and sodium bisulfite, to initiate and promote the chemical reaction. The selection of this catalyst combination is based on in-depth research on its chemical properties and catalytic efficiency, as well as their performance under specific reaction conditions.
[0057] In order to ensure the optimization of the catalytic effect, we carefully calculated and optimized the amount of catalyst added. In the embodiment, the amount of catalyst added was determined to be 0.5% of the total weight of ethylene and vinyl acetate monomers. This ratio is the result of multiple experiments, and is intended to ensure that the concentration of the catalyst in the reaction system is neither too low to play the expected catalytic effect, nor too high to cause unnecessary side reactions or contamination of the product.
[0058] In addition, we also took into account the ratio between ammonium persulfate and sodium bisulfite to achieve the best catalytic effect. In the experiment, it was found that when the weight ratio of ammonium persulfate to sodium bisulfite was 1:1, the activity and balance of the catalyst were significantly improved. This ratio can ensure that during the reaction, the two catalysts can work together to exert the maximum catalytic efficiency.
[0059] In summary, this embodiment can effectively improve the efficiency of the reaction and the quality of the product by precisely controlling the type, addition amount and ratio of the catalyst, thereby achieving the technical objectives of the present application.
[0060] In a preferred embodiment of the present application, the anti-aging agent includes an ultraviolet absorber and an antioxidant.
[0061] It is understandable that the anti-aging agent used in the present embodiment mainly comprises ultraviolet light absorber and antioxidant. These ingredients can effectively prevent the performance degradation and life shortening caused by ultraviolet radiation and oxidation of the product during long-term use. By adding ultraviolet light absorber and antioxidant to the anti-aging agent, the weather resistance and durability of the product can be significantly improved, ensuring that it can maintain good stability and service life under various environmental conditions. This preferred combination can not only improve the performance of the product, but also extend its service life, reduce the frequency of maintenance and replacement, thereby bringing more economical and convenient use experience to the user.
[0062] In a preferred embodiment of the present application, the method for preparing the admixture for concrete anti-sticking comprises:
[0063] Wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture;
[0064] Mixing butyl acrylate, polyoxyethylene stearate and a surfactant to form a mixed liquid;
[0065] Adding the basic admixture into the mixed liquid while stirring to obtain a mixture;
[0066] Add the defoamer, toughening agent and anti-aging agent into the mixture, and continue stirring until the mixture is completely uniform to obtain an admixture for concrete anti-sticking.
[0067] It is understood that the present embodiment specifically relates to a preparation procedure of an admixture for improving the bonding properties of concrete. The preparation process first includes carefully mixing raw materials such as wollastonite, talcum powder, volcanic ash and diatomaceous earth. This step requires that the various raw materials are fully mixed in a certain proportion to ensure the uniformity of the admixture. Subsequently, the mixed raw materials are ground to ensure that the fineness of the powder meets the technical requirements for subsequent use, thereby obtaining a basic admixture powder. Next, butyl acrylate, polyoxyethylene stearate and a surfactant are used to mix these components in a preferred proportion, and they are fully emulsified by stirring to form a stable mixed liquid. The key to this step is to ensure the compatibility of various chemical components and the overall fluidity of the mixed liquid. Then, the previously prepared basic admixture powder is gradually added to the mixed liquid while continuously stirring. This process requires stirring while adding, in order to allow the admixture powder to fully react with the mixed liquid and form a uniform mixture. Finally, to further improve the concrete's anti-bonding properties, while also enhancing its toughness and aging resistance, defoamers, toughening agents, and anti-aging agents are added to the mixture, and stirring continues until the mixture becomes completely homogeneous. Through this series of steps, the final result is an admixture that is suitable for use in concrete and can effectively prevent bonding. This admixture not only improves the workability of concrete, but also provides long-term anti-bonding protection after the concrete hardens, thereby improving the overall performance of the concrete structure.
[0068] In a preferred embodiment of the present application, wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture, and the particle size of the basic admixture is 50-100 μm.
[0069] It can be understood that, in this embodiment, raw materials such as wollastonite, talcum powder, volcanic ash and diatomaceous earth are uniformly mixed through fine industrial operations. In this process, this embodiment pays attention to the ratio between the raw materials to ensure that each raw material can play the maximum effect in the mixing process. Subsequently, the mixed raw materials are ground, and efficient grinding equipment is used in the grinding process to make the raw material particles reach a fine degree, thereby obtaining the required basic admixture. The particle size range of this basic admixture is strictly controlled between 50 and 100 microns. This particle size range can ensure that the admixture can exert excellent performance in subsequent applications. By strictly controlling the particle size of the basic admixture, the quality of the final product can be guaranteed to be stable and meet the high standards of industrial production.
[0070] In a preferred embodiment of the present application, during the preparation process, when butyl acrylate, polyoxyethylene stearate and a surfactant are stirred to form a mixed liquid, the stirring temperature is 30-50° C. and the stirring speed is 200-400 rpm.
[0071] It is understandable that in the specific preparation process of the present embodiment, first, the three raw materials of butyl acrylate, polyoxyethylene stearate and surfactant are fully stirred to form a uniform mixed liquid. In this process, the temperature and speed of stirring need to be strictly controlled to ensure the mixing effect and product quality. The specific stirring temperature should be controlled between 30-50°C. Too high or too low temperature may affect the reaction performance and mixing effect of the raw materials. At the same time, the stirring speed also needs to be controlled within the range of 200-400 rev / min. Such a speed can ensure that the raw materials are fully mixed and improve the stability and uniformity of the product. Through this preferred stirring condition, the efficiency and product quality of the preparation process can be effectively improved.
[0072] The technical solution of the present invention is described in detail below through specific embodiments.
[0073] Example 1
[0074] This embodiment describes in detail the preparation method of the concrete anti-adhesion admixture of the present invention and its effect in practical application with specific data and operation process.
[0075] 1.1 Material preparation
[0076] First, the required raw materials are prepared, including wollastonite, talc, volcanic ash, diatomaceous earth, butyl acrylate, polyoxyethylene stearate, surfactant, defoamer, toughening agent and anti-aging agent in a weight ratio of 5:2:4:3:6:5:1:0.3.
[0077] Wherein, the surfactant is sodium dodecyl sulfate.
[0078] The anti-aging agents are benzotriazole ultraviolet absorber (Tinuvin P) and antioxidant (copper sulfate).
[0079] The defoaming agent is an organosilicon defoaming agent (MSD-916 polyether modified silicone oil).
[0080] The toughening agent is ethylene-vinyl acetate copolymer; wherein the preparation method of ethylene-vinyl acetate copolymer comprises: mixing ethylene and vinyl acetate monomers in a weight ratio of 7:3, and carrying out polymerization reaction under the action of a catalyst. The catalyst is a mixture of ammonium persulfate and sodium bisulfite, and the addition amount is 0.5% of the total weight of ethylene and vinyl acetate monomers, wherein the weight ratio of ammonium persulfate to sodium bisulfite is 1:1. In the polymerization reaction, the reaction temperature is controlled to be 70°C, and the reaction time is 5 hours, and ethylene-vinyl acetate copolymer is obtained as a toughening agent for standby use.
[0081] 1.2 Preparation of admixture
[0082] First, according to the proportions described in this application, wollastonite, talc, volcanic ash and diatomaceous earth are weighed to ensure that the quality of each raw material is accurate. These raw materials are placed in a mixer, and the mixer is started to mix and stir thoroughly until all the raw materials are completely mixed and uniform without particle agglomeration. Subsequently, the mixed raw materials are sent to a grinder for grinding to a basic admixture with a particle size range of 50-100 μm.
[0083] Next, according to the formula requirements, butyl acrylate, polyoxyethylene stearate and surfactant were weighed and placed in a stirring kettle. The stirring device of the stirring kettle was turned on, the stirring temperature was set to 40±2°C, the stirring speed was set to 300 rpm, and sufficient stirring was performed until the raw materials were completely dissolved and a stable mixed liquid was formed.
[0084] Then, gradually add the previously prepared basic admixture to the mixed liquid in the mixing tank, while keeping the stirring device running continuously, stirring while adding to ensure that the admixture and the mixed liquid can fully contact and mix evenly. When the basic admixture is completely added, continue stirring for a while until the mixture becomes uniform and free of particles.
[0085] Finally, add defoamer, toughening agent and anti-aging agent to the mixture, and the amount of these additives is precisely controlled according to the formula requirements. Continue stirring until the mixture is completely uniform to obtain the final concrete anti-adhesion admixture.
[0086] Test Example 1
[0087] Experimental group: According to the method described in Example 1, we added the prepared admixture to the concrete in a predetermined ratio (the weight ratio of the admixture to the concrete was 2:100), and then prepared and poured the concrete. During the preparation process, we first fully stirred the concrete raw materials according to the conventional proportions. After the concrete mixture was initially formed, the admixture was evenly sprinkled into the mixer, and the mixer was started for thorough stirring to ensure that the admixture was evenly distributed in the concrete. In the pouring process, we strictly followed the conventional concrete pouring method, paying special attention to the uniformity and density of the pouring to avoid voids and cracks. After the pouring is completed, we carry out routine maintenance and care in accordance with the standard requirements for concrete hardening to ensure that the concrete can be fully hardened and reach the expected strength.
[0088] In order to verify the actual effect of the concrete anti-adhesion admixture prepared in this embodiment, we set up a comparative experiment 1. In the comparative experiment, we used ordinary concrete without admixture for preparation and pouring, and marked it as the control group (the rest of the preparation and pouring process was the same as the experimental group). Under the same conditions, we observed and tested the bonding performance and durability of the two groups of concrete.
[0089] After observation and testing, we found that the bonding performance of the experimental group concrete was significantly better than that of the control group, and there was no obvious bonding phenomenon on its surface, and the surface was flat and smooth. At the same time, the durability of the experimental group concrete also showed good performance. Under the same conditions of use, its anti-aging and cracking resistance were better than those of the control group.
[0090] The above results show that the concrete anti-adhesion admixture prepared in this embodiment can effectively prevent the occurrence of concrete bonding, significantly improve the anti-adhesion performance of concrete, and enhance its durability and anti-aging properties. Therefore, the concrete anti-adhesion admixture of the present invention has broad application prospects and market demand.
[0091] In practical applications, we further found that concrete with the admixture of the present invention exhibits excellent anti-bonding properties and can effectively prevent the bonding phenomenon of concrete during the hardening process. At the same time, the admixture can also improve the strength and durability of concrete, thereby extending the service life of the concrete structure.
[0092] In order to further explore the optimal addition ratio of this admixture in concrete, we set up different ratios of admixture and concrete in the experimental group for testing (Comparative Test 2). In Comparative Test 2, we set the addition ratio of the admixture to 1:150, 1:125, 1:100, 1:75 and 1:50, respectively, and marked them as experimental groups A, B, C, D and E (the rest of the preparation and pouring process is the same as the experimental group). Under the same preparation and pouring conditions, we recorded the bonding performance and durability data of each group of concrete.
[0093] During the test, we used professional bond strength testing equipment to measure the bond strength between concrete and formwork, and observed durability indicators such as concrete impermeability, compressive strength and wear resistance at different time periods. All data were recorded and processed in strict accordance with relevant national standards.
[0094] The test results show that compared with the control group without admixtures, the concrete in the experimental group has significantly improved in terms of bonding performance and durability. Among them, the concrete in experimental group C (the ratio of admixture to concrete is 1:100) performed well in all indicators, with its bonding strength increased by about 30%, and its impermeability, compressive strength and wear resistance also improved. However, the concrete in experimental groups A and B has relatively limited improvement due to the small amount of admixture added; although the concrete in experimental groups D and E has significantly improved, the excessive amount of admixture added may increase the cost of concrete and have an adverse effect on the fluidity of concrete.
[0095] In summary, when the concrete anti-adhesion admixture prepared in this embodiment is added to concrete at a ratio of 1:100, it can exert its effect to the maximum extent and significantly improve the bonding performance and durability of concrete. This conclusion has important guiding significance for the production and application of concrete.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. An admixture for concrete anti-adhesion, characterized in that: The raw materials of the admixture include: Wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactants and additives; The surfactant includes sodium alkylbenzene sulfonate, sodium stearate or sodium lauryl sulfate; The auxiliary agents include defoamers, toughening agents and anti-aging agents.
2. The admixture for concrete anti-adhesion according to claim 1, characterized in that: The weight ratio of the wollastonite, talc, butyl acrylate, polyoxyethylene stearate, volcanic ash, diatomaceous earth, surfactant and auxiliary agent is 4-5:1-2:3-4:2-3:5-6:4-5:0.5-1:0.2-0.
3.
3. The admixture for concrete anti-adhesion according to claim 1, characterized in that: The defoaming agent includes an organosilicon defoaming agent or a polyether defoaming agent.
4. The admixture for concrete anti-adhesion according to claim 1, characterized in that: The toughening agent includes ethylene-vinyl acetate copolymer.
5. The admixture for concrete anti-adhesion according to claim 4, characterized in that: The preparation method of the ethylene-vinyl acetate copolymer comprises: Ethylene and vinyl acetate monomers are mixed, and an ethylene-vinyl acetate copolymer is prepared by polymerization reaction under the action of a catalyst; Wherein, the weight ratio of ethylene to vinyl acetate monomer is 7-8:2-3; During the polymerization process, the reaction temperature is 60-80°C and the reaction time is 4-6 hours.
6. The admixture for concrete anti-adhesion according to claim 5, characterized in that: The catalyst is a mixture of ammonium persulfate and sodium bisulfite, and the amount of the catalyst added is 0.5% of the total weight of ethylene and vinyl acetate monomers; Wherein, the weight ratio of the ammonium persulfate to sodium bisulfite is 1:
1.
7. The admixture for concrete anti-adhesion according to claim 1, characterized in that: The anti-aging agent includes an ultraviolet absorber and an antioxidant.
8. The admixture for concrete anti-adhesion according to claim 1, characterized in that: The preparation method of the admixture for concrete anti-sticking comprises: Wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture; Mixing butyl acrylate, polyoxyethylene stearate and a surfactant to form a mixed liquid; Adding the basic admixture into the mixed liquid while stirring to obtain a mixture; Add the defoamer, toughening agent and anti-aging agent into the mixture, and continue stirring until the mixture is completely uniform to obtain an admixture for concrete anti-sticking.
9. The admixture for concrete anti-adhesion according to claim 8, characterized in that: When wollastonite, talc, volcanic ash and diatomaceous earth are mixed and ground into powder to obtain a basic admixture, the particle size of the basic admixture is 50-100 μm.
10. The admixture for concrete anti-adhesion according to claim 8, characterized in that: During the preparation process, when butyl acrylate, polyoxyethylene stearate and a surfactant are stirred to form a mixed liquid, the stirring temperature is 30-50° C. and the stirring speed is 200-400 rpm.
Citation Information
Patent Citations
Shrinkage-reducing type concrete interface treating agent and interface treatment method thereof
CN104261764A
Concrete coating protecting system and construction method
CN108250944A